Turnaround, shutdown and outage management : effective planning and step-by-step execution of planned maintenance operations - Lenahan, Tom (Elsevier/Butterworth-Heinemann, 2006)
Shutdown management is project management of a special kind: managing the repair, replacement or maintenance of critical systems. Manufacturing and process plants, computer systems, airliners, and many other systems must be regularly closed down or taken out of service for planned maintenance operations. This book provides a complete shutdown project planning guide along with a new, detailed model of excellence and step-by-step project guide. In a critical field, this book shows the maintenance manager or project leader how to get the job done correctly. *Covers all aspects of major maintenance project planning, minimizing downtime and improving maintenance schedules *Covers projects ranging from weekend overhauls through to complete plant rebuilds *With detailed checklists and a new step-by-step project guide.